2013
DOI: 10.1007/s10904-013-9995-6
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Stabilities of the Metal Doped Gold Nano-Clusters: M@Au10 (M = W, Mo, Ru, Co)

Abstract: The structures and stabilities of a series of endohedral gold clusters containing ten gold atoms M@Au10 (M = W, Mo, Ru, Co) have been determined using density functional theory. The gradient-corrected functional BP86, the Tao-Perdew-Staroverov-Scuseria TPSS meta-GGA functional, and the hybrid density functionals B3LYP and PBE1PBE were employed to calculate the structures, binding energies, adiabatic ionization potentials, and adiabatic electron affinities for these clusters. The LanL2DZ effective core potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…As for the smaller-sized M@Au n clusters with n < 12, Hossain et al 687 extended the scope of M@Au n cage clusters down to n = 10 with endohedral bicapped tetragonal antiprism or prism structure and related distorted cage configurations, or a pentagonal antiprism structure using LanL2DZ basis set and different exchange-correlation functionals. They found that an M atom (M = W, Mo, Ru, Co) can be encapsulated in Au 10 cage with appreciable binding energies and moderate HOMO−LUMO gaps.…”
Section: Doped Au Cagesmentioning
confidence: 99%
“…As for the smaller-sized M@Au n clusters with n < 12, Hossain et al 687 extended the scope of M@Au n cage clusters down to n = 10 with endohedral bicapped tetragonal antiprism or prism structure and related distorted cage configurations, or a pentagonal antiprism structure using LanL2DZ basis set and different exchange-correlation functionals. They found that an M atom (M = W, Mo, Ru, Co) can be encapsulated in Au 10 cage with appreciable binding energies and moderate HOMO−LUMO gaps.…”
Section: Doped Au Cagesmentioning
confidence: 99%
“…The electronic and geometric properties of gold clusters can be tuned by the introduction of a dopant atom, which also influences the chemical properties of the clusters. For example, the binding energies, as well as the HOMO–LUMO gaps, were found to be enhanced by Mo, Ru, and Co doping . Pd doping also substantially alters the stability patterns of cationic gold clusters .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the binding energies, as well as the HOMO-LUMO gaps, were found to be enhancedb yM o, Ru, and Co doping. [15] Pd dopinga lso substantially alters the stability patterns of cationic gold clusters. [16] Doping of both neutrala nd cationic gold clusters with as ilver atom reduces their reactivityt owards CO, [17,18] while doping neutralg old clusters with vanadium decreases their reactivity towardsC Oi nt he size range of 14 to 20 atoms.…”
Section: Introductionmentioning
confidence: 99%
“…They are shown in Figure . The stability of these BP86 results is supported by different comparison of GGA and GGA‐Hybrid methods on the calculation of gold cluster properties . The structure of [WAu 12 ] ( n = 0) is also shown for comparison.…”
Section: Resultsmentioning
confidence: 76%